Measurement of the total cross section and ρ-parameter from elastic scattering in pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (The European physical journal. C, Particles and fields, 2023)
In a special run of the LHC with $$β ^{\star } = 2.5$$ km, proton-proton elastic-scattering events were recorded at $$\sqrt{s} = 13$$ TeV with an integrated luminosity of $$340~\upmu {\text {b}}^{-1}$$using the ALFA subdetector of ATLAS in 2016. The elastic cross section was measured differentially in the Mandelstam t variable in the range from $$-t = 2.5 · 10^{-4}$$ GeV$$^{2}$$to $$-t = 0.46$$ GeV$$^{2}$$using 6.9 million elastic-scattering candidates. This paper presents measurements of the total cross section $$σ _{\text {tot}}$$, parameters of the nuclear slope, and the $$ρ $$-parameter defined as the ratio of the real part to the imaginary part of the elastic-scattering amplitude in the limit → 0$$. These parameters are determined from a fit to the differential elastic cross section using the optical theorem and different parameterizations of the t-dependence. The results for $$σ _{\text {tot}}$$and $$ρ $$are $$\begin{aligned} σ _{\text {tot}}(pp→ X) = 104.7 ± 1.1 \; \text{ mb },\quad ρ = 0.098 ± 0.011 . \end{aligned}$$σtot(pp→X)=104.7±1.1mb,ρ=0.098±0.011.The uncertainty in $$σ _{\text {tot}}$$is dominated by the luminosity measurement, and in $$ρ $$by imperfect knowledge of the detector alignment and by modelling of the nuclear amplitude.
Veröffentlicht: 26. Mai 2023
*ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, F.L. Castillo, M.M. Czurylo, M. Dunford, S. Franchino, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und sehr viele weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 16.05.2024